2014
DOI: 10.1002/syn.21761
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between serotonin and its metabolite 5-HIAA in the cerebrospinal fluid and [11C]AZ10419369 binding measured with PET in healthy volunteers

Abstract: [(11) C]AZ10419369 is sensitive to pharmacologically enhanced endogenous serotonin levels. Twelve healthy volunteers underwent [(11) C]AZ10419369 PET and lumbar puncture. There were no correlations between [(11) C]AZ10419369 binding and concentrations of serotonin and its metabolite 5-HIAA in cerebrospinal fluid, suggesting that [(11) C]AZ10419369 brain binding does not reflect baseline serotonin levels in cerebrospinal fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Samples from this study underwent a maximum of three freeze thaw cycles which resulted in degradation of serotonin. The serotonin concentrations that were measured were lower than published values [ 41 ] and were 5—tenfold lower than concentrations measured in a larger sample of the ABC biobank study (data not shown here). The samples from the ABC biobank study were analysed after only one thaw cycle.…”
Section: Resultscontrasting
confidence: 72%
“…Samples from this study underwent a maximum of three freeze thaw cycles which resulted in degradation of serotonin. The serotonin concentrations that were measured were lower than published values [ 41 ] and were 5—tenfold lower than concentrations measured in a larger sample of the ABC biobank study (data not shown here). The samples from the ABC biobank study were analysed after only one thaw cycle.…”
Section: Resultscontrasting
confidence: 72%
“…Furthermore, pilot studies in human subjects found no correlation between 5-HT or its metabolite 5-hydroxyindole acetic acid (5-HIAA) in the CSF with [ 11 C]AZ10419369 binding in brain. This indicates that [ 11 C]AZ10419369, and perhaps intrasynaptic 5-HT levels, may not correlate with serotonin and 5-HIAA levels in CSF [83]. More recently zolmitriptan, a selective 5-HT 1B/1D R agonist has been tested in human with [ 11 C]AZ10419369 and no significant occupancy was detected with a 5 mg dose, whereas 4–5% occupancy was found for 10 mg dose [84].…”
Section: Introductionmentioning
confidence: 99%
“…However, with a single dose of 20 mg escitalopram given to healthy human volunteers, there was no radioligand displacement. Furthermore, [ 11 C]AZ10419369 BP ND has not been shown to correlate with concentrations of serotonin and its metabolite 5-HIAA (5-hydroxyindoleacetic acid) in cerebrospinal fluid 45 . Thus, although a change in serotonin concentration cannot be ruled out, the increase in hippocampal BP ND most likely reflects increased 5-HT 1B receptor density after ketamine for MDD.…”
Section: Discussionmentioning
confidence: 99%